THE EFFECT OF RETURN ON EQUITY (ROE) AND DEBT TO EQUITY RATIO (DER) ON STOCK PRICES IN THE PRIVATE BANKING SECTOR THAT ARE CONSISTENTLY LISTED ON THE INDONESIA STOCK EXCHANGE IN THE PERIOD 2020–2024 - Lia Amalia; Bambang Susanto; Nurwathi Nurwathi; Ketut Abimanyu (PT. Altin Riset Publishing, 2026)
Stock prices are one of the important indicators for investors because they reflect the company's current performance as well as future prospects, and are the main consideration in investment decisions. Private banking companies listed on the Indonesia Stock Exchange for the 2020–2024 period have fluctuating share prices and some tend to decline. This condition is influenced by many factors, both internal and external. Therefore, this study aims to know, explain, and analyze the influence of Return on Equity and Debt to Equity Ratio on stock prices in the private banking sector that are consistently listed on the Indonesia Stock Exchange for the 2020– 2024 period. This study uses a quantitative approach with a population of 36 companies and a sample of 25 companies selected through purposive sampling. The analysis method used was multiple linear regression with the help of the EViews 12 program. The results of the study show that partially Return on Equity has a significant positive effect on stock prices with a partial determination coefficient of 56.73%, while the Debt to Equity Ratio has a negative effect of insignificant with a partial determination coefficient of 0.49%. Simultaneously, Return on Equity and Debt to Equity have a significant effect on the stock price with an Adjusted R- Square value of 58.29%, which means that the two variables are able to explain the variation in stock prices together. The novelty of this research is the use of the latest period until 2024 which provides a more up-to-date picture of the performance of private banking in Indonesia.